Electromembrane extraction and capillary electrophoresis with capacitively coupled contactless conductivity detection: Multi-extraction capabilities to analyses trace metals from saline samples - Silva, Macarena; Mendiguchía, Carolina; Moreno, Carlos; Kubáň, Pavel (Electrophoresis, 2018)
Simultaneous electromembrane extraction (EME) of six trace metal cations (Cu2+ , Zn2+ , Co2+ , Ni2+ , Pb2+ , Cd2+ ) from saline samples was investigated. CE with capacitively coupled contactless conductivity detection (C4 D) was used to determine the metals in acceptor solutions due to its excellent compatibility with the minute volumes of acceptor solutions. Bis(2-ethylhexyl)phosphate (DEHPA) was selected as a suitable nonselective modifier for EME transport of target metal cations. Both, the individual effect of each major inorganic cation (Na+ , K+ , Ca2+ , Mg2+ ) and their synergistic effect on EME of the trace metal cations were evaluated. In both cases, a decrease in extraction efficiency was observed when major inorganic cations were present in the sample. This effect was more significant for Ca2+ and Mg2+ . The system was optimized for simultaneous extractions of the six target metals from saline samples (50 mM Na+ , 5 mM Mg2+ , 1 mM K+ , and 1 mM Ca2+ ) and following EME conditions were applied. Organic phase consisted of 1-nonanol containing 1% (v/v) DEHPA, acceptor solution was 1 M acetic acid (HAc) and sample pH was adjusted to 5. Sample was stirred at 750 rpm and EMEs were carried out at extraction potential of 10 V for 20 min. The method presented a repeatability between 8 and 21.8% (n = 5), good linearity in 0.5-10 μM concentration range (R2 = 0.987-0.999) and LOD better than 2.6 nM. Applicability of the EME-CE-C4 D method to the analyses of metal cations in drinking water, seawater, and urine samples was also demonstrated.
Keywords: Saline samples; Saline Solution; Major inorganic cations; Electric Conductivity; elektrická vodivost; solný roztok; DEHPA; CE; Seawater; Urine; pitná voda; mořská voda; elektroforéza kapilární; Metal cations; stopové prvky; Drinking Water; moč; Trace Elements; Electromembrane extraction; Electrophoresis, Capillary